Lassen sich Binnenschiffe optimieren? - Zapp, Kerstin (Deutscher Verkehrs-Verl., 2006)
Wenn der § 6 b des Einkommenssteuergesetzes nun tatsächlich wieder eingeführt wird, könnte es mit der Modernisierung der Binnenschiffsflotte vorangehen. Hoher Wettbewerbsdruck zwingt die Unternehmen der Binnenschifffahrt zur kontinuierlichen Verbesserung ihrer Leistungsfähigkeit. Um die Flotte auf dem neuesten Stand zu halten, kommen entweder der Neubau von Schiffen oder die nachträgliche Umrüstung in Betracht. difu

Will consumtion-driven transport continue growth? Transport forms an essential part of private consumption both directly and indirectly. The role it plays reflects both the development of household incomes and the way they are spent. The article identifies the amount of transport services that goes into the production and the final use of goods and services purchased by private households. Using input-output-techniques, it specifies transport intensities of different categories of household expenditure as well as the production sectors involved in satisfying consumer-induced transport demand. One of the main findings of this analysis is that the provison of transport services, including those rendered by the consumers themselves, accounts for about one-fifth of total consumer expenditure. It is against this background that the article investigates the effects consumer behaviour in an ageing society is likely to have on the growth of transport demand in the period up to 2020. difu difu
Keywords: Verkehr; Wasserverkehr; Verkehrstechnologie; Schiffbauindustrie; Innovation; Steuerrecht; Binnenschifffahrt